Cold, wind, and sun exposure: Managing and preventing skin damage - Snowise, M.; Dexter, W. W. (The Physician and Sportsmedicine, 2004)
Outdoor athletes, through the course of their training and competition, are constantly battling environmental effects. Cold and wind exposure can lead to frostbite, which may not be immediately apparent if the skin grows numb. Other common cold-induced conditions include Raynaud's phenomenon, cold-induced urticaria, and chilblains. Summer athletes and athletes participating at higher altitudes need to be especially vigilant for sunburn. Physicians should know when to withhold athletes from play to prevent further damage. By teaching prevention strategies, clinicians can help their patients safely enjoy outdoor sports.